2020
DOI: 10.2147/ott.s272514
|View full text |Cite
|
Sign up to set email alerts
|

<p>Zeaxanthin Induces Apoptosis via ROS-Regulated MAPK and AKT Signaling Pathway in Human Gastric Cancer Cells</p>

Abstract: Background Zeaxanthin, a carotenoid commonly found in plants, has a variety of biological functions including anti-cancer activity. Purpose This study aimed to investigate the potential mechanisms of zeaxanthin in human gastric cancer cells. Methods CCK-8 assay was used to examine the cytotoxic effect of zeaxanthin on human gastric cancer cells. Flow cytometry was used to analyse AGS cell cycle distribution and apoptosis status. Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 42 publications
1
34
0
1
Order By: Relevance
“…The increase of phosphorilated JNK, ERK1/2 or p38 membrane expression could lead to an augmented pro-oxidative process inside the tumor cells, detrimental to the survival of tumor cells. Zeaxanthin was able to regulate the increase of JNK and p38 expression in gastric tumor cells through the increase of ROS levels [ 59 ], and this confirms our hypothesis. Overall, the effect of 1 and 2 on A375 melanoma cells in vitro raises questions about the opportunity of their employment as antitumor agents, and downstream effects of these pathways need to be explored as well.…”
Section: Discussionsupporting
confidence: 85%
“…The increase of phosphorilated JNK, ERK1/2 or p38 membrane expression could lead to an augmented pro-oxidative process inside the tumor cells, detrimental to the survival of tumor cells. Zeaxanthin was able to regulate the increase of JNK and p38 expression in gastric tumor cells through the increase of ROS levels [ 59 ], and this confirms our hypothesis. Overall, the effect of 1 and 2 on A375 melanoma cells in vitro raises questions about the opportunity of their employment as antitumor agents, and downstream effects of these pathways need to be explored as well.…”
Section: Discussionsupporting
confidence: 85%
“…epNPs have been reported to contain various biologically active molecules [13,14,16,17]. Lutein and zeaxanthin, the xanthophylls present in corn [28,29], are known to exhibit antitumor effects through regulation of cell cycle or cell apoptosis [42][43][44]. It has been reported that zeaxanthin induced cell cycle arrest at the G2/M phase and apoptosis through the ROS-mediated MAPK, AKT, NF-κB, and STAT3 signaling pathways [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expressions of Cyclins, and CDKs are related to cell cycle [18]. For example, The down-regulation of CDK2, CDK4 and Cyclin B1 can be inhibited by the development of breast cancer [19].…”
Section: Discussionmentioning
confidence: 99%